The transition from children to young people living with home mechanical ventilation - Åsa Israelsson-Skogsberg; Andreas Palm; Magnus Ekström; Agneta Markström; Berit Lindahl (International Journal of Qualitative Studies on Health & Well-Being)
Purpose This study aimed to examine how young people living with Home Mechanical Ventilation experience the transition from childhood to young adulthood in relation to everyday life, perceived health and transition into adult professional healthcare. Methods Nine young adults (three females and six males aged 18–31) were interviewed, and data was primary analysed using phenomenological hermeneutics. In the actual study, data was reworked using secondary analysis as described by Beck. Two interviewees were ventilated invasively and six non-invasively, and one was treated with continuous positive airway pressure (CPAP). Results The results are presented in two main categories. First; moving towards adulthood; and second, To handle changes in health and healthcare contacts. The study highlights the importance of ongoing social relations and being part of a socializing and physically active community. The transfer from paediatric to adult healthcare was solid and worked out well but was a process in which the participants struggled to find their own voice. Conclusions The transition into adulthood is a sensitive and challenging time for young people with HMV, but stable, close relationships and a well-organized transfer can enable this group to feel safe and able to find and use their own voice.